1983
DOI: 10.1203/00006450-198303000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Genetic Damage from Multivitamin Solutions Exposed to Phototherapy Illumination

Abstract: Summarysubsequently washed with PBS and each flask supplemented withThe ability of standard phototherapy illumination to produce damage in intracellular DNA is well established. In this study, the addition of a dilute solution (1:6400) of a clinically-used multivitamin concentrate to human KB cells was found to enhance the generation of single-strand DNA breaks produced by broad-spectrum fluorescent light. The effect of the exogenous photosensitizing agent (multivitamins) was blocked by the enzyme catalase; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…The weak affinity of RB for nucleic acid is consistent with the finding of Kuratomi and Kobayashi (16) that only one RB molecule is bound to every 500 nucleotide base pairs of DNA in solutions of low ionic strength. Weak RB–DNA binding is also consistent with reports that RB sensitizes the formation of both RB–nucleic acid adducts and single strand breaks (17,18). Our attempts to measure a binding constant of RB via a Scatchard analysis was unsuccessful because of the weak binding of the dye.…”
Section: Discussionsupporting
confidence: 90%
“…The weak affinity of RB for nucleic acid is consistent with the finding of Kuratomi and Kobayashi (16) that only one RB molecule is bound to every 500 nucleotide base pairs of DNA in solutions of low ionic strength. Weak RB–DNA binding is also consistent with reports that RB sensitizes the formation of both RB–nucleic acid adducts and single strand breaks (17,18). Our attempts to measure a binding constant of RB via a Scatchard analysis was unsuccessful because of the weak binding of the dye.…”
Section: Discussionsupporting
confidence: 90%
“…Photolysis of riboflavin and nucleic acids leads to the formation of flavin adducts to AT rich regions of DNA and to the generation of single-strand breaks. The single-strand breaks may well be due to the action of superoxide anion or hydrogen peroxide, , which are also formed upon photolysis of riboflavin. Riboflavin and light sensitize the killing of mammalian cells. , Analysis of the nucleic acids of these cells reveals guanine oxidation and strand breaks. , Interest in this photochemistry has recently surged due to reports that riboflavin can sensitize the inactivation of viruses in the presence of transfusable blood products with acceptable recovery of plasma protein, platelet, and red cell function…”
Section: Introductionmentioning
confidence: 99%
“…Riboflavin has been implicated in toxicity when taken as part of a standard multivitamin preparation. In this situation, riboflavin may be involved in photodynamic damage to DNA, but only in synergism with other multivitamin components, because it has been shown that high levels of riboflavin alone are unable to damage DNA [33].…”
Section: Discussionmentioning
confidence: 99%